2022
DOI: 10.1016/j.gpb.2022.02.004
|View full text |Cite
|
Sign up to set email alerts
|

LDHA Desuccinylase Sirtuin 5 as a Novel Cancer Metastatic Stimulator in Aggressive Prostate Cancer

Abstract: Prostate cancer (PCa) is the most commonly diagnosed genital cancer in men worldwide. Around 80% of the patients who developed advanced PCa suffered from bone metastasis, with a sharp drop in the survival rate. Despite great efforts, the detailed mechanisms underlying castration-resistant PCa (CRPC) remain unclear. Sirtuin 5 (SIRT5), an NAD+-dependent desuccinylase, is hypothesized to be a key regulator of various cancers. However, compared to other SIRTs, the role of SIRT5 in cancer has not been extensively s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
1
21
0
1
Order By: Relevance
“…As in breast cancer, SIRT5 was found to be highly expressed in prostate tumor tissues compared to normal prostate tissues [ 99 ]. However, in contrast, recent studies have revealed that SIRT5 expression is downregulated in advanced prostate cancer [ 100 , 101 ], suggesting that SIRT5 downregulation is dependent on the progression or stage of the prostate cancer cells. These findings may indicate a tumor-stage-dependent role of SIRT5 in prostate carcinogenesis.…”
Section: Mechanistic Roles Of Sirtuins In Breast and Prostate Cancermentioning
confidence: 93%
See 2 more Smart Citations
“…As in breast cancer, SIRT5 was found to be highly expressed in prostate tumor tissues compared to normal prostate tissues [ 99 ]. However, in contrast, recent studies have revealed that SIRT5 expression is downregulated in advanced prostate cancer [ 100 , 101 ], suggesting that SIRT5 downregulation is dependent on the progression or stage of the prostate cancer cells. These findings may indicate a tumor-stage-dependent role of SIRT5 in prostate carcinogenesis.…”
Section: Mechanistic Roles Of Sirtuins In Breast and Prostate Cancermentioning
confidence: 93%
“…Conversely, a more recent study demonstrated that SIRT5 expression reduces the migration and invasion of PC3 prostate cancer cells [ 101 ]. This was found to occur via SIRT5 desuccinylation of LDHA to reduce its activity, culminating in the growth reduction and survival of prostate cancer cells [ 101 ].…”
Section: Mechanistic Roles Of Sirtuins In Breast and Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, no mechanistic insight was provided regarding the role of LDHA in the onset and progression of prostate cancer. 132 …”
Section: Biological Activities and Disease Relevance Of Sirt5mentioning
confidence: 99%
“…The observed effects were ascribed to the higher activity of lactate dehydrogenase (LDH) A, which is activated upon succinylation at Lys118 and is a demonstrated substrate of SIRT5. Nonetheless, no mechanistic insight was provided regarding the role of LDHA in the onset and progression of prostate cancer …”
Section: Biological Activities and Disease Relevance Of Sirt5mentioning
confidence: 99%